Recognition and Memory for Briefly Presented Scenes - Potter, Mary C (Frontiers in Psychology, 2012)
Three times per second, our eyes make a new fixation that generates a new bottom-up analysis in the visual system. How much is extracted from each glimpse? For how long and in what form is that information remembered? To answer these questions, investigators have mimicked the effect of continual shifts of fixation by using rapid serial visual presentation of sequences of unrelated pictures. Experiments in which viewers detect specified target pictures show that detection on the basis of meaning is possible at presentation durations as brief as 13 ms, suggesting that understanding may be based on feedforward processing, without feedback. In contrast, memory for what was just seen is poor unless the viewer has about 500 ms to think about the scene: the scene does not need to remain in view. Initial memory loss after brief presentations occurs over several seconds, suggesting that at least some of the information from the previous few fixations persists long enough to support a coherent representation of the current environment. In contrast to marked memory loss shortly after brief presentations, memory for pictures viewed for 1 s or more is excellent. Although some specific visual information persists, the form and content of the perceptual and memory representations of pictures over time indicate that conceptual information is extracted early and determines most of what remains in longer-term memory.